2005
DOI: 10.3137/ao.430204
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation comparisons between the 2001 and 2002 and the 1961 and 1988 Canadian prairie droughts

Abstract: The 2001 and 2002 Canadian Prairie droughts were unusual climatological events in terms of their extreme precipitation anomalies and extraordinary persistence. Over the west-central Prairie Provinces, well below normal precipitation was recorded for a remarkable eight consecutive seasons from autumn 2000 to summer 2002. Analysis of the mid-tropospheric circulation during these droughts indicates that the patterns were markedly different from those associated with the severe, multi-season Prairie droughts of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Previous studies have suggested that Canada experienced one of its most serious and extensive droughts on record in 2001 and that the most severely affected areas occurred in the Canadian Prairies, where the 2001 drought followed two to three consecutive years of below-average rainfall. Some areas of central Canada suffered the driest August on record and western Canada suffered the second consecutive year with the most severe drought on record in 2002 (22). For eastern Canada, Girardin et al (23) showed that climate warming and increases in the amount and frequency of precipitation during the last century had no significant impact on the severity of summer drought.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that Canada experienced one of its most serious and extensive droughts on record in 2001 and that the most severely affected areas occurred in the Canadian Prairies, where the 2001 drought followed two to three consecutive years of below-average rainfall. Some areas of central Canada suffered the driest August on record and western Canada suffered the second consecutive year with the most severe drought on record in 2002 (22). For eastern Canada, Girardin et al (23) showed that climate warming and increases in the amount and frequency of precipitation during the last century had no significant impact on the severity of summer drought.…”
Section: Discussionmentioning
confidence: 99%
“…Bonsal and Wheaton (2005) reported that, unlike the typical 1961 and 1988 droughts of the Canadian prairies, where the formation of ridges and troughs had a key role, the 2001-2002 drought on the Canadian prairies had no relationships to large-scale circulation patterns. Instead, the drought was caused by a unique circulation pattern related to a northward extension of a persistent drought of the continental United States.…”
Section: Prairie Droughtmentioning
confidence: 98%
“…1). The particular focus was on central Alberta (centred in the Edmonton area) because this region experienced anomalously cold periods during both the most recent -2005(Bonsal and Wheaton, 2005 and 2009 (Wittrock et al, 2010) Prairie droughts. Furthermore, the only long-term radiosonde station for the agricultural region of the Prairies is located at Stony Plain (WSE, WMO ID 71119), Alberta (see Fig.…”
Section: Data and Methods A Study Areamentioning
confidence: 99%
“…However, anomalously cold periods have also been documented during recent severe drought events over this region. These include periods within the well-documented 1999-2005 drought (e.g., Bonsal and Wheaton, 2005;Hanesiak et al, 2011) and that of 2009 (Wittrock et al, 2010). In both cases, mention was only made in passing of such periods, and there was no investigation of the factors leading to them.…”
Section: Introductionmentioning
confidence: 99%